2020
DOI: 10.1093/jjco/hyaa112
|View full text |Cite|
|
Sign up to set email alerts
|

Venous thromboembolism in cancer patients: report of baseline data from the multicentre, prospective Cancer-VTE Registry

Abstract: Background The Cancer-VTE Registry evaluates the occurrence and management of venous thromboembolism in Japanese participants with major solid tumors. Using Registry data, we evaluated the frequency of concurrent venous thromboembolism in cancer patients prior to treatment initiation by cancer type. Methods The Cancer-VTE Registry is an ongoing (March 2017–September 2020) prospective cohort study using a nationwide, multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
67
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 26 publications
9
67
2
1
Order By: Relevance
“… 20 , 21 VTE events mostly occur during hospitalization, including the perioperative period, and subsequent examinations or treatments, which support that hospitalization is an independent risk factor for VTE. 22 , 23 , 24 In addition, most VTE events in this study were found in the lower extremities which is in agreement with previously reported studies. 25 , 26 Therefore, we have the same recommendations as previous studies, 25 which is that lower‐extremity ultrasonography is probably required for screening post‐surgical DVT cases during hospitalization.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 20 , 21 VTE events mostly occur during hospitalization, including the perioperative period, and subsequent examinations or treatments, which support that hospitalization is an independent risk factor for VTE. 22 , 23 , 24 In addition, most VTE events in this study were found in the lower extremities which is in agreement with previously reported studies. 25 , 26 Therefore, we have the same recommendations as previous studies, 25 which is that lower‐extremity ultrasonography is probably required for screening post‐surgical DVT cases during hospitalization.…”
Section: Discussionsupporting
confidence: 93%
“…VTE is a major source of postoperative morbidity and mortality for patients undergoing thoracic surgery 20,21 . VTE events mostly occur during hospitalization, including the perioperative period, and subsequent examinations or treatments, which support that hospitalization is an independent risk factor for VTE 22–24 . In addition, most VTE events in this study were found in the lower extremities which is in agreement with previously reported studies 25,26 .…”
Section: Discussionsupporting
confidence: 91%
“…PE has a multifactorial etiology with many independent risk factors associated with venous thromboembolism (VTE), such as surgery, trauma, hospitalization, malignant neoplasm with or without chemotherapy, and the use of central venous catheters [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, VTE is an independent prognostic factor of mortality in cancer patients. Thus, cancer patients with VTE have a shorter overall survival than cancer patients without VTE at the same tumor stage with the same treatment [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, DVT rarely occurs in patients with various cancers, such as breast, prostate, and colorectal cancers (10,18,26,30,36). A study shows that in 9,735 patients with cancer (such as colorectal, lung, stomach, pancreatic, breast, and gynecologic cancers), the DVT incidence is 5.2% in Japan (37). In terms of patients with breast cancer who underwent surgery, another study exhibits that the 2-month cumulative DVT incidence is ∼0.15% in the USA (26).…”
Section: Discussionmentioning
confidence: 99%